Consumer culture theory - Schouten, John; Martin, Diane (Associate Professor of marketing); Belk, Russell W. (Emerald, 2014)
The chapters in this volume have been selected from the best papers presented at the 9th Annual Consumer Culture Theory Conference held at the home of Aalto University in Finland in June 2014. The theme of the conference was Mapping Consumer Culture. The diverse interpretive research and theory represented in this volume provides the reader with intellectually stimulating opportunities to examine the intersections between a variety of theories and methods that represent the cutting edge in consumer research. These studies draw on an array of qualitative methodologies including ethnography, netnography, narrative and visual analysis, phenomenology, and semiotics. The substantive topics represent crucial issues for our times including understanding and navigating cultural diversity and cultural perspectives on co-creating market value.
Keywords: Consumption (Economics) -- Congresses.; Consumption (Economics) -- Social aspects -- Congresses.; Consumer behavior -- Congresses.; Consumer culture; elektronické knihy; electronic books